A study on the role of Communication in Business Management (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Effective communication plays a crucial role in the success of business management. This study delves into the significance of communication within the realm of business management, exploring its impact on various aspects such as leadership, team dynamics, organizational culture, and decision-making processes. Through a comprehensive review of existing literature and analysis of real-world case studies, this study aims to elucidate the intricate interplay between communication and business management. The findings underscore the importance of clear, transparent, and efficient communication channels in fostering a productive work environment, enhancing employee engagement, and achieving organizational objectives. Additionally, the study highlights the emergence of digital communication platforms and their implications for modern business management practices. By recognizing communication as a cornerstone of effective leadership and managerial process, this study offers valuable insights for businesses striving to optimize their management strategies in an increasingly dynamic and interconnected global landscape.